Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Molecular doping in few-molecule polymer-dopant complexes shows reduced Coulomb binding - Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Coulomb binding energy is reduced when a few-molecule integer charge transfer complex (ICTC) is formed.
Keywords: Materials Chemistry; General Chemistry

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Externally controlled Lotka-Volterra dynamics in a linearly polarized polariton fluid - Pukrop, Matthias; Schumacher, Stefan (Physical Review E)